The Non-N6-Methyladenosine Epitranscriptome Patterns and Characteristics of Tumor Microenvironment Infiltration and Mesenchymal Transition in Glioblastoma - Xu, Jianye; Gao, Zijie; Liu, Kaining; Fan, Yang; Zhang, Zongpu; Xue, Hao; Guo, Xing; Zhang, Ping; Deng, Lin; Wang, Shaobo; Wang, Huizhi; Wang, Qingtong; et al. (Frontiers in Immunology, 2022)
Background: An increasing number of RNA modification types other than N6-methyladenosine (m6A) modification have been detected. Nonetheless, the probable functions of RNA modifications beyond m6A in the tumor microenvironment (TME), mesenchymal (MES) transition, immunotherapy, and drug sensitivity remain unclear. Methods: We analyzed the characteristics of 32 non-m6A RNA modification regulators in 539 glioblastoma (GBM) patients and the TME cell infiltration and MES transition patterns. Using principal component analysis, a non-m6A epitranscriptome regulator score (RM score) model was established. We estimated the association between the RM score and clinical characteristics, TME status, GBM subtypes, and drug and immunotherapy response. Results: Three definite non-m6A RNA modification patterns associated with diverse biological pathways and clinical characteristics were identified. The high RM score group was characterized by a poor prognosis, enhanced immune infiltration and the MES subtype. Further analysis indicated that the high RM score group had a lower tumor mutation burden as well as a weaker response to immunotherapy. The higher RM score group may benefit more from drugs targeting the EGFR and WNT signaling pathways. Conclusion: Our study exposed the potential relationship of non-m6A RNA modification regulators with clinical features, TME status and GBM subtype and clarified its therapeutic value.